Thermoregulatory responses in elite cross-country skiers during international competitions and training - Schobersberger, Wolfgang; Valtonen, Maarit; Köck, Anika; Racinais, Sebastien; Pitsiladis, Yannis; Verdoukas, Panagiotis; Muniz-Pardos, Borja; Mäki-Heikkilä, Rikhard; Ihalainen, Johanna K.; Gagnon, Dominique; Dünnwald, Tobias (Frontiers in Physiology, 2025)
BackgroundThe aim of this study was to describe the thermoregulatory responses of elite athletes during competitions and training of the international cross-country skiing FIS Scandinavian Cup in Finland, held under cold (subzero) ambient conditions.MethodsThe core and skin temperatures were continuously recorded during two competition formats—a 10-km race (n = 18; 10 m, 8 f) and a 20-km race (n = 14; 9 m, 5 f)—and during training (n = 11; 7 m, 4 f) using electronic temperature pills and temperature sensors fixed on the chest, arm, hand, and thigh, respectively. The heart rate and skiing speed were continuously recorded using heart rate monitors with integrated GPS technology. Ambient temperatures during the measuring period ranged from −13.0 °C to −1.3 °C.ResultsThe mean core temperature (Tcore) increased significantly during the 10-km classic (39.0 °C ± 0.4 °C) and the 20-km freestyle (39.2 °C ± 0.7 °C) races (all p < 0.001) and during trainings (38.3 °C ± 0.5 °C). In contrast, skin temperature decreased in all four body parts (all p < 0.001), with the greatest decreases measured on the thigh [18.7 °C ± 4.1 °C (10-km race), 20.7 °C ± 4.6 °C (20-km race), and 18.5 °C ± 3.2 °C (training)]. During both races, the heart rate significantly increased over time while the racing speed decreased (p < 0.001, respectively). The mean skin temperature of the thigh correlated with skiing speed in the 10-km (r = 0.573, p = 0.041) and the 20-km (r = 0.682, p = 0.021) races.ConclusionIn summary, despite low ambient temperatures under real competition and training conditions, the athletes exhibited high heat generation, which enabled them to maintain a high core temperature. In contrast, the skin temperature dropped sharply during competitions and trainings. The association between the low mean skin temperature and the lower racing speed should be investigated further.